2023
DOI: 10.1111/1462-2920.16516
|View full text |Cite
|
Sign up to set email alerts
|

Glacier as a source of novel polyethylene terephthalate hydrolases

Xiaoyan Qi,
Mukan Ji,
Chao‐Fan Yin
et al.

Abstract: Polyethylene terephthalate (PET) is a major component of microplastic contamination globally, which is now detected in pristine environments including Polar and mountain glaciers. As a carbon‐rich molecule, PET could be a carbon source for microorganisms dwelling in glacier habitats. Thus, glacial microorganisms may be potential PET degraders with novel PET hydrolases. Here, we obtained 414 putative PET hydrolase sequences by searching a global glacier metagenome dataset. Metagenomes from the Alps and Tibetan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…Similarly, ancestor 10_543 is separated by 14 mutations from its closest relative with PETase activity (10_544 with N29R, V30A, L33F, S34G, S36D, E65Q, I68V, I88N, E99R, N106D, H107Y, R111D, T115A, S137T); of the 14 mutations associated with gain-of-function in the background of 10_543, none are specifically shared with gain-of-function mutations in either 55_547 or 35_442 and only three gain-of-function mutations occur at the same position (positions 29, 33 and 107). This suggests that (i) there are numerous (and diverse) molecular mechanisms by which PETase activity can emerge from an ancestral cutinase without PETase activity, (ii) these mechanisms are not obviously associated with a restructuring of the enzyme active site and (iii) PETase activity is readily evolutionarily accessible within the cutinase family, consistent with recent observations of PETases that have emerged from cutinase backgrounds 11,12 .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, ancestor 10_543 is separated by 14 mutations from its closest relative with PETase activity (10_544 with N29R, V30A, L33F, S34G, S36D, E65Q, I68V, I88N, E99R, N106D, H107Y, R111D, T115A, S137T); of the 14 mutations associated with gain-of-function in the background of 10_543, none are specifically shared with gain-of-function mutations in either 55_547 or 35_442 and only three gain-of-function mutations occur at the same position (positions 29, 33 and 107). This suggests that (i) there are numerous (and diverse) molecular mechanisms by which PETase activity can emerge from an ancestral cutinase without PETase activity, (ii) these mechanisms are not obviously associated with a restructuring of the enzyme active site and (iii) PETase activity is readily evolutionarily accessible within the cutinase family, consistent with recent observations of PETases that have emerged from cutinase backgrounds 11,12 .…”
Section: Resultssupporting
confidence: 80%
“…Cutinases have garnered significant interest due to their ability to hydrolyse both aromatic and aliphatic polyesters 9 . Cutinases of bacterial 5,9,10 , fungal 7 , and metagenomic [11][12][13] origins have been studied for their PETase activity, including Thc_Cut1 and Thc_Cut from Thermobifida cellulosilytica 5 , TfCut2 from Thermobifida fusca 5 , HiC from Humicola insolens 14 , FsC from Fusarium solani pisi 15 , and LCC from leaf-branch compost metagenome 16 . However, extant cutinases are often unsuitable for direct use in industrial processes, necessitating optimisation to improve properties such as catalytic efficiency 17 , stability under harsh conditions 18,19 , and to alleviate product inhibition 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Even in glaciersone of the most extreme remote places on Earth -414 putative PET hydrolase sequences were recently mined from global glacier metagenome dataset. 81 Enzymatic depolymerization of PET generally has higher efficiency at temperatures higher than glass transition temperature of PET (T g ), which is >60 °C in water. 82 In these conditions, degree of crystallinity is reduced due to greater malleability of polymeric chains, so the ester bonds are more exposed for enzyme attack.…”
Section: Biological Depolymerization Of Petmentioning
confidence: 99%
“…Even in glaciers – one of the most extreme remote places on Earth – 414 putative PET hydrolase sequences were recently mined from global glacier metagenome dataset. 81…”
Section: Recapturing Pet Building Block Monomers From Plastic Wastesmentioning
confidence: 99%
“…Metagenomic mining approaches to search for plastic-degrading enzymes have already yielded promising results, as Popovic et al [75] and Hajighasemi et al [76] used a set of environmental metagenomes to find new carboxylesterase families including enzymes with PLA-and polycaprolactone-degrading activity. Moreover, by screening metagenomes from compost piles, Sonnendecker et al [18] found a highly active polyester hydrolase that completely hydrolyzes amorphous PET films into terephthalic acid, and Qi et al [77] discovered new PET hydrolases in a glacial metagenome with low sequence identity to known active PET hydrolases, possibly representing a new PET hydrolase class.…”
Section: Plos Onementioning
confidence: 99%